Association of T3/T4 ratio with inflammatory indicators and all-cause mortality in stroke survivors - Zhang, Sheng; Su, Zhongzhou; Wen, Xianqiang (Frontiers in Endocrinology, 2025)
BackgroundAbnormal thyroid hormone levels may occur in critical illness, which may have an interactive relationship with inflammatory reaction. At present, the relationship between triiodothyronine (T3)/thyroxine (T4) ratio and inflammatory indicators and all-cause mortality of stroke survivors is still unclear.MethodsWe obtained the relevant data of the respondents from 2007 to 2012 through the National Health and Nutrition Examination Survey (NHANES) database for statistical analysis. The ratio of T3/T4, a continuous variable, is transformed into three groups of classified variables, namely Q1, Q2 and Q3. The relationship between T3/T4 ratio and mortality was analyzed by Log-Rank test and K-M survival curve. Pearson correlation analysis was used to analyze the correlation between T3/T4 ratio and white blood cell (WBC), Neutrophil-to-Lymphocyte Ratio (NLR), systemic immune-inflammation index (SII) and neutrophil percentage-to-albumin ratio (NPAR). Cox univariate and multivariate analysis was used to identify independent risk factors for all-cause mortality in stroke survivors and a nomogram was drawn. Restricted cubic spline (RCS) curve was drawn to determine whether there was a linear relationship between T3/T4 ratio and mortality and the best cut-off value. Subgroup analysis showed the difference between the T3/T4 ratio and all-cause mortality among subgroups and a forest plot was drawn. The mediation effect analysis was used to analyze whether the ratio of T3/T4 could mediate the survival time through inflammatory indicators.ResultsAccording to the inclusion and exclusion criteria, a total of 267 people were included in the study, with a mortality rate of 49.06% (131/267), an average survival time of 111.22 ± 3.19 months, and a median survival time of 130 ± 11.27 months. The Log-Rank test and K-M survival curve showed that there were statistical differences among the Q1, Q2, and Q3 groups of the T3/T4 ratio (x2 = 16.32, p<0.001), and the lower the T3/T4 level, the shorter the survival time. Pearson correlation analysis showed that the T3/T4 ratio had a linear relationship with NLR, SII, and NPAR, and only had a weak correlation with NPAR (r = -0.31, p<0.001). Cox univariate analysis showed that age, marital status, race, cancer, T3/T4 ratio, NPAR and all-cause mortality were related. Multivariate regression analysis showed that age ≥ 60 years, race of non-Hispanic black, low T3/T4 ratio (p = 0.014, HR = 0.92, 95% CI = 0.87~0.98) and high NPAR (p = 0.009, HR = 2.50, 95% CI = 1.26~4.99) were independent risk factors for all-cause mortality. The RCS curve shows that the ratio of T3/T4 is linearly correlated with mortality, and the optimal cutoff value of T3/T4 is 12.97. Subgroup analysis showed that T3/T4 ratio is more likely to affect the survival of stroke survivors with BMI 18.5~28. Mediation effect analysis showed that there was a mediation effect between T3/T4 ratio, NPAR and survival time. The effect size of T3/T4 directly affecting survival time is 78.45%, and the effect size of T3/T4 indirectly affecting survival time through NPAR is 21.55%.ConclusionsT3/T4 ratio is an independent risk factor for all-cause mortality in stroke survivors, especially in the people with BMI 18.5~28. T3/T4 ratio may mediate the survival time through NPAR level. Therefore, monitoring thyroid function is beneficial to the management of stroke survivors.